What Do Animals and Plants Know, Predict and Transmit? - Laugrand, Frédéric; Simon, Lionel (Anthropologica, 2020)
Taking stock of the research conducted in anthropology and related sciences in recent decades, this introduction examines the skills that are attributed to animals and plants by humans. On the one hand, the boundaries between Man and Nature have become more porous, and an increasing number of scientists are recognising the intelligence of these living beings. On the other hand, the categories used to measure this intelligence are inadequate and biased. A few ethnographic fragments taken from fieldwork carried out, in particular, among Indigenous people of the Philippines, Indonesia and Colombia are discussed, confirming this observation. Then, the contributions of the authors of this special issue are briefly presented. These authors call for a renewed reflection on animal and plant skills from the perspective of shared and interacting environments and worlds. Their aim is to deepen reflection on the anthropology of the living.